Association between lower extremity muscle strength and knee loading during 180° pivot turn in female players - Leppänen, M.; Parkkari, J.; Krosshaug, T.; Vasankari, T.; Kannus, P.; Pasanen, K. (International Journal of Athletic Therapy & Training, 2024)
Sufficient muscle strength is suggested to reduce frontal plane knee loading during change of direction maneuvers. However, it is currently not thoroughly understood if lower extremity strength is associated with increased frontal plane knee biomechanics during change of direction in youth female team sport players. The objective of this cross-sectional study was to investigate the influence of maximal muscle strength on knee valgus angle and knee abduction moment during 180° pivot turn in 106 youth female team sport players. Lower hip abductor strength, lower knee extensor strength, and higher knee flexor strength were associated with increased knee valgus. Higher knee flexor and leg press strength were associated with increased knee abduction moment. The study found associations between both decreased and increased lower extremity muscle strength and frontal plane knee biomechanics. However, these associations could explain only 20% of the variance in frontal plane knee biomechanics at best.